1978
DOI: 10.1007/bf00417849
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic consequences of mutations towards antibiotic-hypersensitivity in Serratia marcescens

Abstract: Various mutants (oxas) were isolated from Serratia marcescens SM-6 by selecting for hypersensitivity towards oxacillin. All mutants found are highly pleiotropic and able to yield spontaneous revertants which behave like the wild-type. Mutant W 1421 mostly studied shows the following phenotypic properties not found in the wild-type: (1) The growth is hypersensitive to various antibiotics, detergents and dyes which differ remarkably in their chemical structure and antibacterial action-mechanism, (2) the cells ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…From our results and other worker's studies (1,3,6), it was suggested that the hypersensitivity to p-lactam antibiotics of hypersensitive mutants is associated with not only the loss of p-lactamase productivity, but also the increased susceptibility to lysis by detergents such as SDS (7) or sarkosy (1) which attack the outer membrane. …”
supporting
confidence: 68%
See 1 more Smart Citation
“…From our results and other worker's studies (1,3,6), it was suggested that the hypersensitivity to p-lactam antibiotics of hypersensitive mutants is associated with not only the loss of p-lactamase productivity, but also the increased susceptibility to lysis by detergents such as SDS (7) or sarkosy (1) which attack the outer membrane. …”
supporting
confidence: 68%
“…1, B and C). The increased susceptibility to lysis by detergents such as SDS has been considered to be due to outer membrane mutation in the mutants from E. coli (1), P. aeruginosa (3), and S. marcescens (6). There- fore, triton-, sarkosyl-, and SDS-insoluble membrane fractions of the strain Pre and the parents strain were prepared by treatment with concentrations of 2°1, of each detergent for 30 min at 25 C as described by Whitfield et al (5), and applied to a continuous system of SDS-polyacrylamide gel electrophoresis (SDS-PAGE) (2) using 12(() acrylamide (Fig.…”
mentioning
confidence: 99%
“…A few nonpigmented colonies which produced protease were found, but these were rare. The correlation between pigmentation and protease production has been observed by others (40). The rleationship between the unstable pigmentation phenotype and expression of the protease is not clear.…”
Section: Resultsmentioning
confidence: 83%
“…Lipase activity (39) and synthesis of the pigment prodigiosin (unpublished observation) also decrease in rough strains of S. marcescens. Furthermore, a decrease in exocellular nuclease (16) and prodigiosin (38) production by S. marcescens has been correlated with an increase in the growth temperature from 30 to 37°C, parallel with alterations in LPS structure (this study).…”
Section: Methodsmentioning
confidence: 86%